Growth model of the new member states: Challenges and prospects - Andrea Elekes; Péter Halmai (Intereconomics, 2013)
This paper reviews the strong pre-crisis economic growth in the new EU member states and assesses whether the growth model can continue to be successful after the crisis. The analysis shows that a new growth model for the region will be needed, ideally one that focuses on raising domestic savings, implementing structural reforms to increase potential growth and rebalancing growth towards tradable sectors.
Keywords: 330